Access to Palliative Care for Cancer Patients Living in a Northern and Rural Environment in Ontario, Canada: The Effects of Geographic Region and Rurality on End-of-Life Care in a Population-Based Decedent Cancer Cohort. (February 2019) - Conlon, Michael SC; Caswell, Joseph M; Santi, Stacey A; Ballantyne, Barbara; Meigs, Margaret L; Knight, Andrew; Earle, Craig C; Hartman, Mark
Background: Access to palliative care has been associated with improving quality of life and reducing the use of potentially aggressive end-of-life care. However, many challenges and barriers exist in providing palliative care to residents in northern and rural settings in Ontario, Canada. Aim: The purpose of this study was to examine access to palliative care and associations with the use of end-of-life care in a decedent cohort of northern and southern, rural and urban, residents. Design: Using linked administrative databases, residents were classified into geographic and rural categories. Regression methods were used to define use and associations of palliative and end-of-life care and death in acute care hospital. Setting/Participants: A decedent cancer cohort of Ontario residents (2007-2012). Results: Northern rural residents were less likely to receive palliative care (adjusted odds ratio [OR] = 0.90, 95% confidence interval [CI]: 0.83-0.97). Those not receiving palliative care were more likely to receive potentially aggressive end-of-life care and die in an acute care hospital (adjusted OR = 1.20, 95% CI: 1.02-1.41). Conclusions: Palliative care was significantly associated with reduced use of aggressive end-of-life care; however, disparities exist in rural locations, especially those in the north. Higher usage of emergency department (ED) and hospital resources at end of life in rural locations also reflects differing roles of rural community hospitals compared with urban hospitals. Improving access to palliative care in rural and northern locations is an important care issue and may reduce use of potentially aggressive end-of-life care.